Tanggung Jawab Pemberi Kerja Atas Kewajiban Menyediakan Transportasi Bagi Pekerja - Efendi, Vadila; Kuahaty, Sarah Selfina; Fataruba, Sabri (Faculty of Law Universitas Pattimura, 2025)
As an employer or entrepreneur, Article 76 paragraph (4) of the Manpower Law states that employers are obliged to provide pick-up and drop-off transportation for female workers who go to and from work between 23.00 and 05.00. In fact, PT Indomarco Prismatama does not provide transportation for workers. Normative juridical research methods and the nature of descriptive analytical writing using a statutory approach and a conceptual approach The research results showed that: Companies or employers are individuals, entrepreneurs, legal entities, or other bodies that employ workers by paying wages or remuneration and are obliged to be responsible for realizing workers' rights, especially providing shuttle transportation for workers who work late at night between 23.00 and 05.00. PT Indomarco Prismatama as an employer is responsible for fulfilling its obligations towards workers' rights by providing transportation for workers. In fact, it was not implemented so that the company is absolutely responsible for all the consequences it causes because it does not carry out its obligations, namely providing transportation for workers. The legal consequences if PT Indomarco Prismatama does not prepare transportation for its employees, namely that the security and safety of employees is not guaranteed, can cause undesirable things and then legal consequences for the company itself, namely because the company does not comply with the law, then the company will be given sanctions, both administrative sanctions and criminal sanctions. Apart from that, as a result of this incident, the legal rules that had been established did not function or did not run optimally.